Black Cat. Vol. 09, Showdown at the old castle - Yabuki, Kentaro (Viz Media, 2007)
"Train Heartnet, also known as Black Cat, was an infamous assassin for a secret organization called Chronos until he abandoned that cold blooded existence ... The Chronos assault team ... find[s] themselves battling a beast created by nanomachine technology. Sensing danger, Train appears on the scene. But instead of taking sides, Train has his own agenda."--P. [4] of cover.